ESPÍRITOS DO UNIVERSO RESPONSÁVEIS PELO DESTINO: ESTUDO EXEGÉTICO EM COLOSSENSES 2.8-3.4 - ALMEIDA, RAFAEL SILVA (2015)
This dissertation will examine the Greek expression ta. stoicei/a tou/ ko,smou, "the elements of the world", which appears in the letter of Colossians verses 8-20 of the second chapter. There will be an exegetical study of the biblical pericope 2:8-3:4 of the letter as well as a historical analysis specifically the term stoicei/a. The study of this expression is important to be able to understand the Colossians philosophy mentioned in Cl 2:8. The Christian church in the city of Colossae, is part of a syncretic religious social context. This syncretism is clearly seen in magic texts as the Greek Magical Papyri, very common in Minor Asia region, where the Colossian church was situated. Religious syncretism, involving Jewish and pagan beliefs, reflects the basis of this philosophy. The author of the letter to the Colossians refutes the belief in "elements of the world" and the subservience to them. Among other beliefs, it was believed that these "elements" could influence events on land and the fate of people. Issues involving ascetic practices, worship of angels and observance of the liturgical calendar, give the contours of this philosophy. The writer emphasizes the Lordship of Christ and his works in favor of Colossian Christians, who gave them a good destination. Moreover, the Colossian Christians are guaranteed a freedom that could not be curtailed by any other religious beliefs. So the works of Christ and his lordship are the main arguments used by the author of the letter, in order to say to Christians in Colossae that they no longer need to fear their fate and to submit to the "elements of the world".